Cloning and characterization of rad21 an essential gene of Schizosaccharomyces pombe involved in DNA double-strand-break repair. - Birkenbihl, R P (1992)
Analysis of the Schizosaccharomyces pombe chromosomes by pulsed field gel electrophoresis showed that the fission yeast has a very efficient DNA double-strand-break (dsb) repair system, which properly restores the three chromosomes after they are degraded by gamma-irradiation. The radiation-sensitive mutant rad21-45 is deficient in this repair pathway but is capable of cell-cycle arrest in G2 following DNA damage. We cloned the rad21 gene by complementing the radiation sensitivity of the rad21-45 mutant. The plasmid-borne gene completely reestablished the DNA dsb repair pathway. The rad21 gene was localized to chromosome III by hybridization. The transcript is 2.5 kb long and expressed at a moderate level. The 1884-bp open reading frame encodes a 628 amino acid, very acidic peptide with a calculated molecular mass of 67,854 D. The rad21 gene shows no significant homology to other known nucleotide or peptide sequences. The inability of the mutant to perform efficient DNA repair is caused by a single base substitution, which changes wild-type isoleucine67 into threonine in the mutant. Deletion of the genomic rad21 gene showed that it is essential for mitotic growth of S.pombe.